Validation and pilot feasibility study of a novel screener to assess diet, lifestyle and mental health in people living with and beyond cancer: Study protocols - Alice Chaplin; Janna Wordsworth; Lara Prohens; Antònia Obrador-Hevia; Monica Guillot; Ignacio Ricci-Cabello; Albert Sesé; Dora Romaguera (PLoS ONE, 2025)
Background and aim Current clinical care may not address behavioural and psychosocial elements which can influence quality of life (QoL) and recurrence risk of people living with and beyond cancer (PLWBC). There is a lack of validated tools to assess diet, lifestyle and mental health in PLWBC. We have developed a screener to identify individuals who may need further support beyond cancer recurrence. The aim is two-fold: 1) validate the screener in PLWBC; and 2) carry out a pilot feasibility study (PFS) to explore the impact of a lifestyle complex intervention (diet, physical activity and mental health components) on the QoL of PLWBC. Methods The study will be carried out at the University Hospital Son Espases (Spain) in PLWBC. A face validity study (n = 15) will assess construct interpretation, completion time, and acquiescence of the screener. For construct validity and reproducibility analysis (n = 100), participants will answer the screener together with validated diet, lifestyle, and mental health questionnaires for comparison. Body composition, physical activity, strength and cortisol levels will be assessed using validated instruments. All participants will answer the screener 7–10 days later for reproducibility analysis. Participants will then be randomized (1:1) to the Low Intervention (LI) or the High Intervention (HI) for the PFS study. LI will receive general advice regarding diet, lifestyle and mental health, and HI will receive individual and group sessions with specialised health professionals. Participants will be followed for three months. Primary outcomes include: 1) validity and reproducibility of the screener; and 2) feasibility of a complex intervention to improve QoL of PLWBC. Secondary outcomes include changes in screener answers and body composition. Discussion A validated screener which detects PLWBC’s needs could be used in follow-up care plans. The PFS will inform on the recruitment of participants and identify potential shortfalls of the design and efficacy. Trial registration ClinicalTrials.gov NCT06582498.